Exploring the infusion of thinking skills and EQ in lecturers’ instructions at a premiere polytechnic / Zetty Harisha Harun...[et al.] - Harun, Zetty Harisha; Abdullah, Marziana; Harun, Robekhah; Primsuwan, Phaveena (Universiti Teknologi MARA, Kedah, 2013)
in the polytechnic’s ESL classroom in terms of the lecturers’ classroom instructions in relation to their questioning techniques and responses. This is looked at how much thinking and EQ are being infused through the lecturers’ instructions during the lesson. A study which consists of three methods of data collection; observation of the lessons, video-taped recording of the same lessons and the lesson transcriptions was conducted to investigate the matter. Five ESL lecturers from Politeknik Premiere Sultan Salahuddin Abdul Aziz Shah were chosen as subjects of this study. They were observed once in their classroom during which their lessons were video- taped for analysis. The instrument used is known as GRAMEITS. A correlational analysis was also carried out through the bivariate analysis using SPSS Version 17. This is to determine the reliability and validity of the data and the instrument. Thus, a reliability r=0.999 between the two raters indicates a high reliability and validity.